Psychological profiling of hackers via machine learning toward sustainable cybersecurity - Hani, Umema; Sohaib, Osama; Khan, Khalid; Aleidi, Asma; Islam, Noman (Frontiers in Computer Science, 2024)
This research addresses a challenge of the hacker classification framework based on the “big five personality traits” model (OCEAN) and explores associations between personality traits and hacker types. The method's application prediction performance was evaluated in two groups: Students with hacking experience who intend to pursue information security and ethical hacking and industry professionals who work as White Hat hackers. These professionals were further categorized based on their behavioral tendencies, incorporating Gray Hat traits. The k-means algorithm analyzed intra-cluster dependencies, elucidating variations within different clusters and their correlation with Hat types. The study achieved an 88% accuracy in mapping clusters with Hat types, effectively identifying cyber-criminal behaviors. Ethical considerations regarding privacy and bias in personality profiling methodologies within cybersecurity are discussed, emphasizing the importance of informed consent, transparency, and accountability in data management practices. Furthermore, the research underscores the need for sustainable cybersecurity practices, integrating environmental and societal impacts into security frameworks. This study aims to advance responsible cybersecurity practices by promoting awareness and ethical considerations and prioritizing privacy, equity, and sustainability principles.